Financial inclusion and physical health functioning among aging adults in the sub-Saharan African context: Exploring social networks and gender roles. - Razak M Gyasi; Siaw Frimpong; Gilbert Kwabena Amoako; Anokye M Adam (PLoS ONE)
Background It remains poorly understood how financial inclusion influences physical health functioning in later life in sub-Saharan African context and whether the association differs by gender and social relationships. We aim 1) to examine the associations of financial inclusion with functional impairment during older age in Ghana; and 2) to evaluate whether gender and social networks modify this association. Methods The cross-sectional analyses are based on a sample (N = 1,201) of study participants aged 50 years and over (M = 66.5 years, SD = 11.9, 63.3% female) deriving from the 2016-2017 AgeHeaPsyWel-HeaSeeB Study. Ordinary least squares (OLS) regression analyses with interactions were performed to estimate the link between financial inclusion and functional health and how the association is modified by gender and older age social networks. Results The mean financial inclusion score was 1.66 (SD = 1.74) in women and 2.33 (SD = 1.82) in men whilst mean activities of daily living (ADL) score was 13.03 (SD = 4.99) and 14.85 (SD = 5.06) in women and men respectively. We found that financial inclusion was associated with decreases in ADL (total sample: β = -.548, p < .001; women: β = -.582, p < .001; men: β = -1.082 p < .001) and instrumental ADL (IADL) (total sample: β = -.359, p = .034; women: β = -.445, p = .026 but not in men). Social networks significantly moderated the association of financial inclusion with ADL such that the financially included who were embedded in a stronger constellation of social networks were 6% less likely to report ADL impairment compared to those with weaker social networks (β = -.062, p = .025). Conclusions The study provides empirical evidence for a better understanding of the association between financial inclusion and physical health functioning in the context of later life social networks. Interventions for functional health through financial inclusion in sub-Saharan Africa should include improving interpersonal and social networks for older adult and also through gender lenses.